Haemodynamic effects of oral salbutamol alone and in combination with sublingual isosorbide dinitrate in patients with severe congestive cardiac failure. Issue 2 (February 1980) - Stephens, J D; Banim, S O; Spurrell, R A
Abstract : To examine possible augmentation of the effects of isosorbide dinitrate by salbutamol, haemodynamic measurements were made in 10 patients with severe chronic congestive cardiac failure who received isosorbide dinitrate 2.5 to 25 mg sublingually and salbutamol 4 to 12 mg orally, alone and in combination. Isosorbide dinitrate reduced mean left ventricular filling pressure from 29 to 18 mmHg and increased mean cardiac index from 1.7 to 2.0 1/min per m2, with no significant change in mean heart rate. Systemic arterial mean pressure fell from 85 to 72 mmHg. Salbutamol increased cardiac index from 1.8 to 2.2 1/min per m2. There was no significant change in left ventricular filling pressure, heart rate, or systemic arterial pressure. Compared with control, combined isosorbide dinitrate and salbutamol reduced left ventricular filling pressure from 27 to 19 mmHg and increased cardiac index from 1.8 to 2.7 1/min per m2, with no significant change in heart rate. Systemic arterial pressure fell from 82 to 75 mmHg. The reduction in left ventricular filling pressure by combined treatment was similar to that produced by isosorbide dinitrate alone, but the increase in cardiac index was significantly greater than that produced either by isosorbide dinitrate alone or salbutamol alone. Combined sublingual isosorbide dinitrate and oral salbutamol have an additive effect in improving left ventricular performance in patients with severe chronic congestive cardiac failure.